REAKTUALISASI MASJID SEBAGAI PENDIDIKAN ISLAM NON-FORMAL DI KABUPATEN BONE - Adrianti, Ririn; Ridhwan, Ridhwan; Halidin, Ali; Fatimah, Fatimah (Institut Agama Islam Negeri (IAIN) Bone, 2022)
AbstractThis article discusses the actualization of mosques as non-formal Islamic education in Bone Regency. This type of research is a qualitative research and uses a pedagogical, historical, and sociological approach. Data was collected using observation, interviews, and documentation. The data obtained, processed using the method of reduction, data presentation, and verification and drawing conclusions.The results showed that the implementation of mosque-based non-formal Islamic education, namely the Makmur mosque, Nurul Hudal mosque, and Nurul Ikhsan mosque, mosque in the form of book recitation activities, taklim assemblies, and Al-Qur’an education were carried out. in accordance with the management of non-formal Islamic education, namely planning an activity, compiling an activity structure, carrying out activities and being monitored by activity managers and paying attention to the structure of non-formal Islamic education based on mosques, namely having teaching staff, having curriculum, subject matter, learning methods and strategies.